Suluh Kacang - Rosli, Muhamad Afiq Afnan (College of Creative Arts, 2023)
The ‘Sulur Kacang’ motif is frequently found in Malaysian wood and silver carvings. The de- sign was inspired by the spirals and hangings found on walnut trees. This design element can be found in jewellery, trunks, and traditional wooden structures such as entry facades, window frames, and wall panels. The narrow line along the design’s background represents a protective mechanism. This sculpture, which combines Malaysian and Indonesian motifs, was inspired by ‘Sulur Kacang’ and the crashing waters along the coast. The famous beaches of Bali served as inspiration for the design of the ‘Sulur Kacang’ which features a wave pattern as its primary element. Rattan, bamboo, and timber were utilised to construct the sculpture.